2021
DOI: 10.1111/jocd.14012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Langerhans cells role in vitiligo and its relationship to NB‐UVB

Abstract: Background: Langerhans cells (LCs) are antigen-presenting cells that are characterized by CD1a and CD207/langerin expression. The disturbance in the communication network among keratinocytes, melanocytes, and antigen-presenting cells may be involved in vitiligo pathogenesis. Aims:The current work aims to detect and quantify LCs in involved skin of patients affected by vitiligo before and after treatment with NB-UVB using CD1a immunohistochemistry, in addition to correlate percentage of LCs with the clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous studies investigating the quantity of LCs in vitiligo-affected skin have reported contradictory results, with some observing a reduction in the percentage of epidermal LCs [ 13 ] and others reporting an increase in epidermal LCs [ 11 , 12 ]. To resolve this issue and determine whether there are changes in LC numbers in the epidermis of patients with vitiligo, we obtained formalin-fixed paraffin-embedded tissue from eight lesional skin samples of non-segmental vitiligo in the progressive state, ten lesional skin samples of non-segmental vitiligo in the stable state, and five normal skin samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies investigating the quantity of LCs in vitiligo-affected skin have reported contradictory results, with some observing a reduction in the percentage of epidermal LCs [ 13 ] and others reporting an increase in epidermal LCs [ 11 , 12 ]. To resolve this issue and determine whether there are changes in LC numbers in the epidermis of patients with vitiligo, we obtained formalin-fixed paraffin-embedded tissue from eight lesional skin samples of non-segmental vitiligo in the progressive state, ten lesional skin samples of non-segmental vitiligo in the stable state, and five normal skin samples.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Prignano et al and Seite et al [ 12 , 29 ] reported that narrow-band ultraviolet B (NB-UVB) and UVA1 treatment reduced LC density, redistributed main LCs, and slightly altered morphology of LCs in vitiligo. However, recently, in a study with 20 vitiligo patients and 10 age- and sex-matched controls, Shoeib et al [ 13 ] reported a reduction in LC percentage in skin affected by vitiligo and found no statistical change in LC percentage after NB-UVB therapy. Thus, the quantity and role of epidermal LCs in vitiligo has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 13 This modulates cutaneous sensory transduction, 33 influencing both inflammatory responses and the immune and endocrine systems as a whole. 20 , 34 , 35 The tape with magnetic particles (TMP) is an elastic adhesive bandage with particles with magnetic properties. When TMP comes in contact with electromagnetic fields, such as those generated by living beings, it creates a magnetic flux, that, in turn, produces a magnetic induction proportional to the variation of the magnetic flux.…”
Section: Introductionmentioning
confidence: 99%